Application of concentrated solar energy in postprocessing of selective laser melted Ti6Al4V alloy through simultaneously gas nitriding and heat treatment - Chicos, Lucia-Antoneta; Rodríguez, Jose; Cañadas, Inmaculada; Galindo, Jose; Cempura, Grzegorz; Kruk, Adam; Ziętara, Maciej; Gruszczyński, Adam; Pop, Mihai Alin; Zaharia, Sebastian Marian; Lancea, Camil (Springer Science and Business Media LLC, 2025)
Additive manufacturing is revolutionizing sustainable manufacturing by optimizing production processes and enhancing material and energy efficiency, reducing waste, and lowering resource consumption. Its integration with renewable energy sources further amplifies these benefits by reducing time, energy consumption and minimizing ecological impact. Currently, no studies have reported on high-temperature gas nitriding or the combined thermochemical and thermal treatment of Ti6Al4V alloy produced by selective laser melting (SLM) in a solar furnace (SF) using Concentrated Solar Energy (CSE) as a clean, renewable energy source. This paper presents the first study on the simultaneous thermal and gas nitriding thermochemical treatment of the Ti6Al4V ELI alloy manufactured by SLM, carried out in a SF using CSE and reducing post-processing times. Samples made of SLM Ti6Al4V ELI alloy were subjected to gas nitriding in the SF at temperatures of 900, 1050, and 1200 °C with short holding times of 5, 10, and 15 min. SEM–EDS, XRD analyses, and micro Vickers hardness tests conducted on samples nitrided in SF, using CSE, confirmed the development of a nitrogen compound layer and a nitrogen diffusion zone, accompanied by a significant increase in microhardness, but achieved within a considerably shorter processing time. Total post-processing time for gas nitriding in the SF is up to 73% shorter than in conventional furnace. Simultaneously with gas nitriding thermochemical treatment, as-fabricated microstructure of Ti6Al4V ELI alloy, an acicular α′ martensite, was transformed into α + β with different morphologies. This paper demonstrates the integration of high-temperatures solar energy technology into the thermal post-processing of Ti6Al4V alloy, manufactured by the SLM additive manufacturing process, through nitriding thermochemical treatments
Keywords: Concentrated solar energy; Additive manufacturing; Ti6Al4V; Selective laser melting; Nitriding; Post-processing